DEVELOPMENT OF INFRASTRUCTURE SUPPORT OF THE WORLD ELECTRONIC LOGISTICS MARKET - OMELCHENKO, VOLODYMYR; OMELCHENKO, HANNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article states that the priority features of the current stage of globalization are informatization, electronicization and logistics of international business, which acts as the latest stage of integration of the world economy, the content of which is to expand virtual flows of resources, resulting in intensified competition in global electronic markets, deepening of interconnections between national economies at the level of social reproduction processes, formation of integrated logistics and electronic networks and their infrastructure. On the basis of the conducted generalizations the state establishments (ministries, departments, etc.), subjects of economic activity forming public infrastructure of the international market of electronic logistics, at cotton enterprises, TNCs, FIGs, etc.), consumers of products / services (individuals), partners (intermediaries), and in its structure the most priority segments are "business business" (B2B) "business consumer" (B2C). On the basis of certain patterns of development of the global e-logistics market, scientific and methodological approaches to the study of the development of infrastructure of national e-logistics markets are substantiated by the criteria: perfection of regulatory support, development of e-business; the state of development of the IT sector; optimality of the segment structure of outsourcing of the electronic logistics market; efficiency of the existing state of infrastructural support of development of the national market of electronic logistics. This allows you to create an information and analytical base to adjust the priorities of the national e-logistics business at the state level.)
Keywords: e-logistics market; e-market infrastructure; outsourcing; IT outsourcing; corporate information systems